Bharatiya nagarik suraksha sanhita, 2023 - Garg,Sandeep (pub.) (New Delhi Commercial law, 2024)
This comprehensive legal resource focuses on the Bharatiya Nagarik Suraksha Sanhita (BNSS) 2023, offering a detailed comparison with the Code of Criminal Procedure 1973. Notable for its innovative features, this book includes tables, a section/alphabetical key, a subject index, etc., making it easier to understand and compare the new legislation with its historical counterpart. It is an invaluable tool for the judiciary, legal professionals, enforcement agencies, government bodies, students, and the general public.
Keywords: Criminal law; Criminal procedure